Development and Validation of a Four Adenosine-to-Inosine RNA Editing Site-Relevant Prognostic Signature for Assessing Survival in Breast Cancer Patients - Wan, Jian; Chen, Shizhen; Zhang, Anqin; Liu, Yiting; Zhang, Yangyang; Li, Qinghua; Yu, Ziqi; Wan, Yuwei; Yang, Lei; Wang, Qi (Frontiers in Oncology, 2022)
Background: Adenosine-to-inosine RNA editing (ATIRE) is increasingly being used to characterize cancer. However, no studies have been conducted to identify an ATIRE signature for predicting cancer survival. Methods: Breast cancer (BRCA) samples with ATIRE profiles from The Cancer Genome Atlas were divided into a training (n=452) and an internal validation cohort (n=311), and 197 additional BRCA patients were recruited as an external validation cohort. The ATIRE signature for BRCA overall survival (OS) and disease-free survival (DFS) were identified using forest algorithm analysis and experimentally verified by direct-sequencing. An ATIRE-based risk score (AIRS) was established with these selected ATIRE sites. Significantly prognostic factors were incorporated to generate a nomogram that were evaluated using the Harrell's C-index and calibration plot for all cohorts. Results: Seven ATIRE sites were revealed to be associated with both BRCA OS and DFS, of which four sites were experimentally confirmed. Patients with high AIRS displayed higher risk of death than those with low AIRS in the training (HR=3.142, 95%CI=1.932-5.111), internal validation (HR=2.097, 95%CI=1.123-3.914) and external validation cohorts (HR=2.680, 95%CI=1.000-7.194). A similar hazard effect of high AIRS on DFS was observed. The nomogram yielded Harrell's C-indexes of 0.816 (95%CI=0.784-0.847), 0.742 (95%CI=0.684-0.799), and 0.835 (95%CI=0.869-0.902) for predicting OS, and 0.767 (95%CI=0.708-0.826), 0.684 (95%CI=0.605-0.763), and 0.635 (95%CI=0.566-0.705) for predicting DFS in the three cohorts. Conclusion: AIRS nomogram could help to predict OS and DFS of patients with BRCA.